Life’s crucial 9 is inversely and linearly associated with female infertility prevalence: a cross-sectional analysis from NHANES 2013–2018 - Bianfang Li; Han Zhai (Scientific Reports)
Abstract Cardiovascular health (CVH) and depression may be associated with female infertility. More recently, it has been suggested that the addition of psychological health assessment to Life’s Essential 8 (LE8), known as Life’s Crucial 9 (LC9), may be clinically relevant. We aimed to explore the association of LC9 with female infertility and whether LC9 has significantly improved predictive ability for infertility compared to LE8 through NHANES 2013–2018. The LE8 was assessed by the approach proposed by the American Heart Association and included 8 CVH components. LC9 added an additional assessment of depression score based on the Patient Health Questionnaire-9 to LE8. Female infertility was diagnosed by self-report. Multivariate logistic regression analyses were used to explore these associations and to calculate odds ratios (ORs) and 95% confidence intervals (CIs). A total of 2088 women of reproductive age were included in the study, with an infertility prevalence of 13.98%.In the fully adjusted model, higher LC9 scores were associated with reduced odds of female infertility. Women in the highest LC9 quartile (Q2, Q3, and Q4) had consistently lower odds of infertility compared to those in the lowest quartile (Q1), with a significant linear trend observed. The components of LC9 that were found to be inversely associated with infertility included sleep health, body mass index, blood glucose, and depression.The relationship between LC9 and infertility was modified by both age and race/ethnicity. However, LC9 did not demonstrate a significant improvement in its predictive value for infertility when compared to LE8.This study indicate that LC9 is associated with a decreased likelihood of female infertility, suggesting its potential as a comprehensive cardiovascular health metric in this context. However, the study also found that LC9 did not significantly enhance the predictive ability for female infertility when compared to the established LE8 framework. These findings suggest that the inclusion of depression assessment in LE8 may not be essential for the prediction and prevention of female infertility, despite the observed association between depression and infertility. This underscores the need for further research to refine the integration of psychological health into cardiovascular health metrics and to explore targeted interventions for improving reproductive outcomes.